PERAN MUI DALAM PERLINDUNGAN KONSUMEN TERHADAP PEMALSUAN LABEL HALAL DI KOTA MAKASSAR PERSPEKTIF SIYASAH SYAR’IYYAH - Husnul Khatimah; Syatar, Abdul; Mustafa, Zulhas’ari; Irfan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
The type of research used is qualitative research (Field Research) with a juridical and syar’i approach. Sources of data obtained directly from research subjects in the field by means of interviews and secondary data obtained from official documents of the Institute for the Assessment of Food, Drugs and Cosmetics of the Indonesian Ulema Council (LPPOM MUI), South Sulawesi Indonesian Ulema Council (MUI SULSEL), scientific journals and articles relevant to this study, the data analysis used is qualitative analysis. The research results show that; 1) The MUI concept in handling food and beverage products that are not labeled halal, that is, socialize regularly and MUI has the authority to determine product halalness through halal fatwa meetings 2) Forms of legal protection for consumers for food and beverage products that do not have a Halal Label, as stated in the Law - Law Number 33 of 2014 concerning guarantees for halal products, as well as giving warning letters, sanctions/fines to business actors who do not follow halal procedures. 3) The perspective of siyasa syar’iyyah regarding food in Islam has been explained in general in the Qur’an and al-Sunnah, in the form of recommendations for eating what is lawful and good (tayyib) and prohibiting eating what is unlawful.